Shrinking windows of opportunity for oak seedling establishment in southern California mountains. Issue 11 (10th November 2016) - Davis, Frank W.; Sweet, Lynn C.; Serra‐Diaz, Josep M.; Franklin, Janet; McCullough, Ian; Flint, Alan; Flint, Lorraine; Dingman, John R.; Regan, Helen M.; Syphard, Alexandra D.; Hannah, Lee; Redmond, Kelly; et al.
Abstract: Seedling establishment is a critical step that may ultimately govern tree species' distribution shifts under environmental change. Annual variation in the location of seed rain and microclimates results in transient "windows of opportunity" for tree seedling establishment across the landscape. These establishment windows vary at fine spatiotemporal scales that are not considered in most assessments of climate change impacts on tree species range dynamics and habitat displacement. We integrate field seedling establishment trials conducted in the southern Sierra Nevada and western Tehachapi Mountains of southern California with spatially downscaled grids of modeled water‐year climatic water deficit (CWDwy ) and mean August maximum daily temperature ( T max ) to map historical and projected future microclimates suitable for establishment windows of opportunity for Quercus douglasii, a dominant tree species of warm, dry foothill woodlands, and Q. kelloggii, a dominant of cooler, more mesic montane woodlands and forests. Based on quasi‐binomial regression models, Q. douglasii seedling establishment is significantly associated with modeled CWDwy and to a lesser degree with modeled T max . Q. kelloggii seedling establishment is most strongly associated with T max and best predicted by a two‐factor model including CWDwy and T max . Establishment niche models are applied to explore recruitment window dynamics in the western Tehachapi Mountains, where these species are currently widespread canopy dominants. Establishment windows are projected to decrease by 50–95%, shrinking locally to higher elevations and north‐facing slopes by the end of this century depending on the species and climate scenario. These decreases in establishment windows suggest the potential for longer‐term regional population declines of the species. While many additional processes regulate seedling establishment and growth, this study highlights the need to account for topoclimatic controls and interannual climatic variation when assessing how seedling establishment and colonization processes could be affected by climate change.